INVESTMENT CHOICE AND PREFERENCES AMONG SALARIED PEOPLE A STUDY OF COLLEGE TEACHERS - Sharma, Mukesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The condition of a nation's financial markets determines its rate of growth. For instance, over the past 20 years, India has experienced incredible growth.(6). Technology, innovation, the launch of new financial products, and the LPG (liberalization, privatization, globalization) strategy are the main drivers of this expansion. In the past, people would make investments according to conventional knowledge, but these days, people invest in a multitude of novel possibilities.(7) Investment is a complicated process, as we all know. The most crucial function in educating children is played by teachers, who belong to the salaried class and receive set incomes.(8) They contribute significantly to the physical, mental, and intellectual development of children.(9) In light of this, the purpose of this work is to explore the investment choices and preferences of college teachers. This paper examines the elements that affect their preferences, awareness, and knowledge about investments, as well as their investment decisions. Data for this research study was collected through questionnaires, and the paper offers suggestions to college teachers regarding their investment choices and preferences.